ANALISIS PENGARUH KEPEMIMPINAN DAN KEDISIPLINAN TERHADAP PRESTASI KERJA MELALUI MOTIVASI KERJA (STUDI PADA PEGAWAI DIVISI OPERASIONAL PT. BNI LIFE INSURANCE) - Rusjianto, Lucki; Supriyadi, Edy; Putriana, Lies (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2019)
The purpose of this study was to determine the effect of leadership, discipline and work motivation on work performance and prove the hypothesis regarding the relationship of research variables: leadership, discipline, motivation and work performance. The study population was all employees in the operational division of PT. BNI Life Insurance recorded 183 employees. The statistical method used in this study is Structural Equation Modeling (SEM) which is operated through the LISREL program. In this study resulted that the variables of leadership, discipline, and work motivation have a positive and significant effect on work performance